2023
DOI: 10.1088/2053-1591/acece0
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanism of refining and modifying in Al–Si–Mg casting alloys with adding rare earth cerium

Abstract: In this paper, Al-7%Si-0.6%Mg-X%Ce (X=0, 0.1 and 0.2) casting alloys were prepared by vacuum induction furnace. Using optical microscopy (OM), X-ray diffractometer (XRD), scanning electron microscopy (SEM), energy spectrometry (EDS), differential scanning calorimetry (DSC) and transmission electron microscopy (TEM), the microstructures of the experimental alloys were studied, and the mechanism of refinement and modification of the alloy were discussed. Results show that AlCeSi2 was formed after adding cerium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The corrosion is mainly concentrated at the grain boundary between the intermetallic compound and matrix aluminum [ 5 , 9 ]. In research on the corrosion of aluminum with the addition of rare-earth elements, it is reported that the low potential difference between the new precipitate phase and aluminum shows a lower corrosion rate compared to the alloy without rare-earth elements and improves corrosion resistance properties [ 11 , 12 , 13 ]. However, most rare-earth elements have high costs and limited reserves, making their application to Al alloys challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion is mainly concentrated at the grain boundary between the intermetallic compound and matrix aluminum [ 5 , 9 ]. In research on the corrosion of aluminum with the addition of rare-earth elements, it is reported that the low potential difference between the new precipitate phase and aluminum shows a lower corrosion rate compared to the alloy without rare-earth elements and improves corrosion resistance properties [ 11 , 12 , 13 ]. However, most rare-earth elements have high costs and limited reserves, making their application to Al alloys challenging.…”
Section: Introductionmentioning
confidence: 99%